Implementasi Kebijakan Pengembangan Objek Wisata Watervang Di Kota Lubuk Linggau - Amelda, Suci; Sakir, Icuk Muhammad; Asteriniah, Femi (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
This well-known Watervang Tourism Object is visited by many tourists. This Watervang tourist attraction is suitable for families, children, as well as young people to relax, fill holidays, or enjoy weekends. Facilities that are continuously equipped and perfected by the management, increase the interest of tourists to enjoy the charm of these tourist objects. According to (lubuklinggaukota.go.id) Tourist attractions in Lubuklinggau City are currently experiencing very good development, as evidenced by the large number of tourists arriving at the tourist attraction. Watervang. This cannot be separated from the announcement of Sebiduk Semare City in the